QCM-D Studies on Polymer Behavior at Interfaces - Liu, Guangming; Zhang, Guangzhao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
QCM-D Studies on Polymer Behavior at Interfaces reviews the applications of quartz crystal microbalance with dissipation (QCM-D) in polymer research, including the conformational change of grafted polymer chains, the grafting kinetics of polymer chains, the growth mechanism of polyelectrolyte multilayers, and the interactions between polymers and phospholipid membranes. It focuses on how QCM-D can be applied to the study of polymer behavior at various solid-liquid interfaces. Moreover, it clearly reveals the physical significance of the changes in frequency and dissipation associated with the different polymer behaviors at the interfaces.
Basic Principles of QCM-D -- Conformational Change of Grafted Polymer Chains -- Grafting Kinetics of Polymer Chains -- Growth Mechanism of Polyelectrolyte Multilayers -- Interactions between Polymers and Phospholipid Membranes.
Keywords: Chemistry; Polymers; Surfaces (Physics).; Chemistry; Polymer Sciences; Surface and Interface Science, Thin Films; Surfaces and Interfaces, Thin Films; Electrochemistry